A Comparison of Innovative Building Design with Implementation of Form-Based Codes: Case Studies of Denver (USA), Hong Kong (HKSAR) and Phuket (Thailand) - Masuwan, Kanokwan; Lertwattanaruk, Pusit (Journal of Architectural/Planning Research and Studies (JARS), 2020)
Concepts and measures for urban planning in Thailand provide the regulation control to land use, open space, transportation, and public utilities. It focuses on governing the usage characteristics and creating a general physical development framework rather than creating tools to meet the specific details of a particular area and promoting the social engagement process. This causes inconsistent physical requirements and stakeholders are not aware of the role and importance of urban development Form-Based Codes (FBCs) are urban planning measures that provide in-depth land use management and urban planning with the goal-setting approaches. It also represents the vision and needs of the city’s residents in order to develop the planning regulations as physical tools toward a more efficient utilization of land, rehabilitation, and promotion of the district identity and improving the quality of life of people in the city. FBCs are, therefore, in response to both the physical and social dimensions. The objective of this research is to study the concepts of FBCs and implement the FBCs to the existing codes and physical characteristics of the case study areas with the focus on understanding the characteristics of applying FBCs in the areas with different limitations. By comparing existing laws and regulations, administration, and physical planning standards of public space and building codes, the two groups of case study areas include Denver, USA where FBCs are enforced, and another group consists of Hong Kong and Phuket, Thailand, where it is possible to adapt FBCs to suit the context and limitations. The analysis of variables based on the conceptual framework of FBCs consists of 1) the concept of urban planning development, considering the duty of the legislators, social participation process and land use, and 2) the components of FBCs consists of reference planning, public space standards, building form standards, administration and specific legal definitions. The study found that Denver has adopted the FBCs concept from the beginning of the city planning process. It used FBCs as a tool for policy making, decision making, and legal regulations issued with details of public space standards and building standards consistent with the identity and physical characteristics of the area. On the contrary, Hong Kong has the main limitation: ownership of land management is owned by the government causing the lack of participation process from the public sector. For Thailand, centralized government structure resulted in the lack of integration from both government agencies and cooperation of the private and public sectors to benefit the development of the area. Physically, both Hong Kong and Thailand are likely to adopt FBCs in conjunction with the existing urban plans. By referring to land use as a base map and using FBCs as a specific plan for the public spaces and building forms which is a physical integration for the special district.